2020
DOI: 10.3390/en13123248
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Environmental Performance of Palm Oil Biodiesel Production in Indonesia: A Life Cycle Assessment Approach

Abstract: The production of palm oil biodiesel in Indonesia has the potential to negatively impact the environment if not managed properly. Therefore, we conducted a life cycle assessment (LCA) study on the production of palm oil biodiesel to assess the environmental performance in Indonesia. Using an LCA approach, we analyzed the environmental indicators, including the carbon footprint, as well as the harm to human health, ecosystem diversity, and resource availability in palm oil biodiesel production. The functional u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Methanol is an essential material in transesterification for biodiesel production. An environmental life cycle assessment study on biodiesel production has shown that methanol is one of the causes of the high environmental pollution of transesterification (Soraya et al, 2014;Siregar et al, 2015;Wahyono et al, 2020). Methanol is a volatile organic compound (VOC); as it evaporates into the atmosphere, it reacts with NOx, water vapor, and sunlight radiation, thereby forming photochemical oxidants (Zou et al, 2015;Wahyono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Methanol is an essential material in transesterification for biodiesel production. An environmental life cycle assessment study on biodiesel production has shown that methanol is one of the causes of the high environmental pollution of transesterification (Soraya et al, 2014;Siregar et al, 2015;Wahyono et al, 2020). Methanol is a volatile organic compound (VOC); as it evaporates into the atmosphere, it reacts with NOx, water vapor, and sunlight radiation, thereby forming photochemical oxidants (Zou et al, 2015;Wahyono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, not all meat substitutes are sustainable. Some contain palm oil, known to increase pollution, GHG emissions and land conversion [ 21 , 22 ], and some may include genetically modified foods, which remain a contentious issue worldwide [ 23 ]. Secondly, certain meat substitutes may be classed as ultra-processed [ 24 ] because of their high fat or sodium content, or on the basis of a long list of what consumers consider “unnecessary ingredients”, i.e., preservatives, sweeteners, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Zentrum für rationelle Energieanwendung und Umwelt (ZREU) has calculated the potential of biomass resources in Indonesia to be around 146.7 million tons/year. Biomass can be produced from sugarcane bagasse, soybean stover, peanut shell waste, palm oil waste biomass (husk, fiber, empty fruit bunches, palm oil mill effluent), coconut stems and midribs, and agricultural waste corn (corncobs, corn stalks, and leaves) can be used as alternative fuels [9]. The results of burning biomass produce biogenic CO2, which is more environmentally friendly than the combustion of fossil fuels which produce fossil CO2 [10].…”
Section: Introductionmentioning
confidence: 99%